1956
DOI: 10.1113/jphysiol.1956.sp005542
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of the growth of collagen in the uterus of the pregnant rat

Abstract: In a previous paper it was reported that rapid formation of collagen took place in the rat's uterus during pregnancy, and that the quantity formed depended upon the number of foetuses present. It was thought probable that mechanical distension by the growing contents played an important part in determining this relationship. No direct evidence was, however, obtained to support this view and it was possible, though perhaps unlikely, that the relation could be entirely explained by local growth of collagen at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1956
1956
1992
1992

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…These results show that: (1) an acute preparation may be satisfactorily used for investigation of factors influencing thyroid function, thus confirming Soderberg (1958); (2) the thyroid responds rapidly to an increased concentration of TSH in the blood; and (3) electrical stimulation of the region of the supraoptico-hypophysial tract in the hypothalamus causes an increase in thyroid activity, as observed by Harris & Woods (1958) (Harkness & Harkness, 1956) suggested that distension is a major factor in stimulating growth of the collagen in the uterus during pregnancy. It is impossible, however, to exclude other local influences, and the present work was designed to test directly the effect of distension.…”
Section: P Society 23 May 1959supporting
confidence: 65%
“…These results show that: (1) an acute preparation may be satisfactorily used for investigation of factors influencing thyroid function, thus confirming Soderberg (1958); (2) the thyroid responds rapidly to an increased concentration of TSH in the blood; and (3) electrical stimulation of the region of the supraoptico-hypophysial tract in the hypothalamus causes an increase in thyroid activity, as observed by Harris & Woods (1958) (Harkness & Harkness, 1956) suggested that distension is a major factor in stimulating growth of the collagen in the uterus during pregnancy. It is impossible, however, to exclude other local influences, and the present work was designed to test directly the effect of distension.…”
Section: P Society 23 May 1959supporting
confidence: 65%
“…It is known that this factor plays an important part in determining the growth of collagen in the uterus in pregnancy , 1956 R. D. HARKNESS AND BRENDA E. MORALEE in the group, the sole criterion for exclusion being the number of foetuses. This procedure is defective in the early stages after parturition as it only gives useful information about the mean values and none about the variability which is largely due to variation in the number of foetal sites.…”
Section: Resultsmentioning
confidence: 99%
“…Thus it appears that under hormonal treatment the uterus behaves like other organs subjected to a stimulus to growth, in showing collagen formation 18-2 277 278 Harkness, 1956b). The relatively small amount of collagen formation which takes place in pregnancy in an empty horn could be produced by progesterone, which is presumably circulating in large amounts, since large amounts are required to maintain pregnancy in spayed animals (Alexander & Frazer, 1954).…”
Section: Discussionmentioning
confidence: 99%